Handmade Traction Wrist Tower - Zolotov, Alexander (Journal of Wrist Surgery, 2018)
The article presents handmade traction wrist tower, made from improvised means, which can be an alternative for expensive branded traction devices. The proposed device can be used successfully for wrist joint arthroscopy, as well as for performing various surgical procedures on the wrist and forearm, when traction is needed. This a Level IV study.
Keywords: wrist tower; wrist arthroscopy; distal radius fracture